On the Validity of Diffusion/Dispersion Tests in Soils - Auriault, J.-L.; Lewandowska, J. (Engineering Transactions, 1997)
In the paper, the validity of dispersion/diffusion parameters identified in the column tests is discussed. Using the experimental data reported in the literature it is shown that in some cases, the continuum approach (the Fickian mode of transport) can not be applied to interpret the test results. In such cases the transport parameters obtained by fitting the experimental results to the macroscopic model (the advection-dispersion equation) are experiment-dependent and can not be considered as intrinsic parameters. In order to illustrate the problem, the calculations of the scale separation parameter introduced in the homogenization theory are performed in four particular cases.